Gender Differences in Psychological and Behavioral Responses of Infected and Uninfected Health-Care Workers During the Early COVID-19 Outbreak - Qiao Huang; Qiao Huang; Li-Sha Luo; Li-Sha Luo; Yun-Yun Wang; Yun-Yun Wang; Ying-Hui Jin; Ying-Hui Jin; Xian-Tao Zeng; Xian-Tao Zeng (Frontiers Media S.A., 2021)
Objective: Understanding gender differences in responses of health-care workers (HCWs) to COVID-19 outbreak is an effective way to promote customized supports.Methods: During February 2020, 103 HCWs infected with COVID-19 (64 females and 39 males) and 535 uninfected HCWs (383 females and 152 males) were recruited in a cross-sectional study. Level of attention, six emotional status, and self-evaluation of eight protective measures were recorded. Multivariable Firth's logistic regressions were applied to explored independent effect of gender.Results: During early outbreak, female HCWs were more likely to give greater attention, adjusted OR:1.92 (95%CI 1.14-3.23) in total HCWs. Higher proportion of anxiety was observed in female HCWs, adjusted OR:3.14 (95%CI 1.98-4.99) for total HCWs, 4.32(95%CI 1.32-14.15) for infected HCWs and 2.97 (1.78, 4.95) for uninfected HCWs. Proportion of pessimism, fear, full of fighting spirit, and optimism were low, and no gender differences were observed. During a later outbreak, a majority of HCWs reported being very familiar with eight protective measures. After training, a proportion of high self-evaluation in hand hygiene, wearing gloves, and surgical masks increased independently in female HCWs, and adjusted ORs were 3.07 (95% CI 1.57-5.99), 2.37 (95% CI 1.26-4.49), and 1.92 (95% CI 1.02-3.62), respectively. Infection status amplified gender difference in anxiety, hand hygiene, and glove wearing.Conclusion: Female HCWs perceived the outbreak seriously, effective emotional and psychological well-ness should be targeted at female HCWs preferentially, and male HCWs should be encouraged to express their feelings and be further trained.